2018
DOI: 10.1093/carcin/bgy077
|View full text |Cite
|
Sign up to set email alerts
|

Dro1/Ccdc80 inactivation promotes AOM/DSS-induced colorectal carcinogenesis and aggravates colitis by DSS in mice

Abstract: Colorectal carcinogenesis is a progressive multistep process involving the sequential accumulation of genetic alterations in tumor suppressor genes and oncogenes. Downregulated by oncogenes 1 (Dro1/Ccdc80) has been shown to be a potent tumor suppressor of colorectal carcinogenesis in the genetic ApcMin/+ mouse model. In ApcMin/+ mice, loss of DRO1 strongly increases colonic tumor multiplicity and leads to the regular formation of adenocarcinoma in the colon. To investigate DRO1's role in chemically induced as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In the present study, we performed transcriptome sequencing to explore the transcriptome changes in CRC cells after NP treatment. We found that the coiled-coil domain containing 80 (CCDC80), a tumor suppressor in CRC, was significantly reduced after NP exposure (Grill et al, 2018). The results of the current study reveal the underlying mechanism of NP exposure in CRC progression and provide novel insights into CRC occurrence and progression.…”
Section: Introductionmentioning
confidence: 68%
“…In the present study, we performed transcriptome sequencing to explore the transcriptome changes in CRC cells after NP treatment. We found that the coiled-coil domain containing 80 (CCDC80), a tumor suppressor in CRC, was significantly reduced after NP exposure (Grill et al, 2018). The results of the current study reveal the underlying mechanism of NP exposure in CRC progression and provide novel insights into CRC occurrence and progression.…”
Section: Introductionmentioning
confidence: 68%
“…CCDC80 has been considered as a multipurpose molecule in vertebrates, mediating diverse developmental processes [23]. Using transcriptional profiling, previous publications have identified that CCDC80 may play a role in tumor inhibition, such as ovarian cancer [24], malignant melanoma [25], thyroid [26] and colorectal carcinoma [27]. CCDC80 is expressed in several types of cells, in particular in preadipocytes and adipocytes, while it is temporarily down-regulated during cell differentiation [16].…”
Section: Discussionmentioning
confidence: 99%
“…In Apc Min/+ mice ubiquitous inactivation of Dro1/Ccdc80 results in early death, a significant increase in the colonic tumor load, and the regular formation of adenocarcinoma in the colon [ 1 ]. Loss of DRO1/CCDC80 increases multiplicity of preneoplastic aberrant crypt foci and colonic tumors in carcinogen-induced colon carcinogenesis and promotes formation of colon adenocarcinoma during inflammation-driven carcinogenesis [ 6 ]. In colon tumors from Apc Min/+ mice loss of DRO1/CCDC80 induces ERK1/2 phosphorylation and leads to c-MYC oncogene activation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the tumor suppressor role of Dro1/Ccdc80 in vivo has always been addressed by ubiquitous gene inactivation in mice [ 1 , 3 , 6 ]. For the study of tumorigenesis this approach implicates Dro1/Ccdc80 deficiency in both the tumor parenchyma and the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%